Design and Implementation of E-House with Photovoltaic-Wind Hybrid System for Smart Microgrid - Dr.G.Karthikeyan, Dr.D.Prasad, P.Kirubakaran (International Journal of Advanced Science and Technology, 2020)
A hybrid Renewable Energy sources (HRES) based on solar and wind energy system is designed in this work. The solar t model is formulated using 170 W PV panels which are connected in series. The wind plant is designed using PMSG motor and AC/DC conversion is carried out using an uncontrolled full-bridge rectifier. The output obtained from these plants are connected to a full bridge VSI. This inverter is controlled using SPWM topology. From the analysis, it is concluded that this proposed system produces a constant output voltage with reduced fluctuations.